Management and outcomes of military penetrating neck injuries: An eleven-year retrospective case note review. Issue 1 (January 2023) - Pickering, Christopher; Muzaffar, Jameel; Reid, Conor; Zakaria, Benjamin; Coulson, Christopher; Sharma, Neil; Breeze, John
Highlights: Penetrating neck injury management of military persons in Iraq and Afghanistan who were seen at deployed UK facilities and evacuated back to UK. CTA was effective at ruling out significant vascular or aerodigestive injury. UK Military surgeons had a low threshold for open neck exploration, even in patients with both a negative CTA and no clinical hard signs. Abstract: Introduction: Penetrating Neck Injuries (PNIs) affected 3.2% of trauma patients attending US and UK deployed medical treatment facilities (MTFs) during the Iraq and Afghanistan conflicts. Injured military personnel requiring aeromedical evacuation for such injuries were managed at the Royal Centre for Defence Medicine (RCDM), Birmingham, UK. The aim of this paper was to review the management of PNI in both deployed MTFs and when evacuated back to the UK. Patients and methods: A retrospective case note review was performed of all military patients who sustained PNI whilst on deployment overseas, and who were subsequently evacuated to RCDM between March 2003 and December 2014. Results: Forty casualties who sustained PNI were identified, of which 28/40 (70%) sustained injury from explosive fragmentation, and 11/40 (28%) from gunshot wounds. Hard signs of PNI were present in 3/40 (7.5%) patients, soft signs in 14/40 (35%), no signs in 12/40 (30%), and unknown signs in 11/40 (28%) patients. Computed tomography angiography (CTA) was used in 39/40 (98%) patients, and was effective at ruling out significant injury, with 100% (29/29) of casualties with a negative CTA not developing vascular or aerodigestive injury. There were 9/29 (31%) patients who had surgical neck exploration despite both a negative CTA and absence of hard signs of PNI. There were 12/40 (30%) patients who required operative intervention at RCDM. Conclusion: UK military surgeons in Role 3 MTFs had a low threshold for surgical exploration, even in the absence of CT findings or hard signs. This was likely due to the high-energy mechanisms responsible for military PNI, in addition to the limited availability of equipment and clinical expertise in visualising the larynx.